Transcriptional analysis of the human D4Z4 and mouse Dux arrays - Hampson, Amanda (2012)
Facioscapulohumeral muscular dystrophy (FSHD) is the third most common form of muscular dystrophy in Caucasians. FSHD is caused by contraction of a 3.3kb repeat array, D4Z4, to below 11 repeat units. Each of these repeat units contains an ORF encoding the DUX4 gene and at the beginning of the work described in this thesis expression of transcripts from the most distal repeat of this D4Z4 array had been reported. However, expression data from the DUX4 gene was new and most research focussed on contraction of the array having a position affect on the expression of neighbouring genes. There is a similar Dux array located in the mouse genome. This array also contains an ORF in each repeat and transcripts from this gene have been detected in a number of different tissues. This array is not present in the same chromosomal location as the D4Z4 array in humans so is unlikely to be a true ortholog, however it is the only Dux array in the mouse genome and may therefore be functionally equivalent. The work described in this thesis provides evidence for transcription from multiple repeats of the D4Z4 array in a human embryonal carcinoma cell line and gives information on the sequence variation within these transcripts. In addition, this work contributes to an understanding of expression from the mouse Dux array. Similar to the human array, expression appears to come from multiple repeat units, and analysis of the sequences amplified by RT-PCR identifies variants which suggest some of these transcripts are non-coding. The aim of this work is to determine whether human DUX4 and mouse Dux genes have equivalent functions with the long-term goal of producing a mouse model for FSHD